Extraction, refining, and fabrication of light metals - Sahoo, Mahi; Pinfold, Peter (Proceedings of the Metallurgical Society of the Canadian Institute of Mining and Metallurgy, 1991)
World-class scientists and engineers from more than six countries presented thirty-five papers on topics such as magnesium casting technology, metal matrix composites, mathematical modelling, solidification and reduction of light metals. Metal matrix composites are an important class of advanced industrial materials and significant advances have been achieved recently on the fabrication and characterization of their microstructures and mechanical properties.